The importance of preventing and controlling biofilm in wounds: Biofilm models and nanotechnology in antibiofilm approaches - Barbosa, D. B. [UNESP]; Agostinho Hunt, A. M.; Berretta, A.; Rodrigues de Camargo, E.; Gorup, L. F.; Monteiro, D. R. [UNESP]; Fernandes, G. L. [UNESP]; Fernandes, R. A. [UNESP]; Kirker, K. R. (Elsevier, 2016)
Biofilms may compromise wound healing, because of their tolerance to antimicrobials. Control of biofilms has been achieved with combinations of drugs and alternative antimicrobial agents. Silver nanoparticles have been the subject of substantial research for medical and health applications, and there is a remarkable international effort underway to verify their safety and to understand how these nanoparticles effectively kill several microorganisms. The use of silver nanoparticles in natural products with medicinal importance is a relatively new concept and is a widely accepted technology with rapid production capabilities and minimum impact on human health and environmental quality. This chapter presents the importance of studying biofilms, especially in chronic wounds using in vitro models, and emphasizes the potential green synthesis of silver nanoparticles.
Keywords: Biofilm; Green; Nanotechnology; Silver; Wound